Farmers’ perceptions on characteristics of cassava (Manihot esculenta Crantz) varieties used for chips production in rural areas in Benin, West Africa - Gnonlonfin, G.J.B.; Koudande, O.D.; Sanni, A.; Brimer, L. (African Journals Online, 2011)
A survey aimed at collecting information about cassava varieties/cultivars and farmers’ perceptions concerning cassava and chemical food safety was conducted in 10 villages located in two agroecological zones in Benin. A structured questionnaire to interview farmers was employed. Out of 100 farmers sampled, most of them relaying on chips as food and source of income were women. Overall, 40% of all farmers marketed chips locally. Tasting was the main technique use by farmers to discriminate cassava varieties including Kpaki Kpika, Kpaki Soan, Logo Guesse Kotorou and BEN 86052. The latter being introduced by research centres. Both bitter and sweet cassava were produced and the sweet varieties being used for chips production by farmers who do perceive bitter cassava as toxic crop. Our results call for more investigations in promoting gender oriented safety and hygiene/sanitation techniques.